PENGARUH PEMBERIAN TERAPI GENERALIS DALAM MENGATASI ANSIETAS KELUARGA PASIEN HEMODIALISA - Qurrotul Aeni; Riani Pradara Jati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
THE EFFECT OF GENERALIST THERAPY IN OVERCOMING FAMILY ANXIETY OF HEMODIALYSIS PATIENTS ABSTRACTHemodialysis is an act of renal replacement therapy that has been damaged, which is to move the patient's blood from his body through a dialiser which occurs by diffusion and ultrafiltration. Patients who undergo activities continuously can experience some psychological problems including anxiety. The study aimed to determine the effect of generalist therapy in overcoming family anxiety of hemodialysis patients in Dr.H Hospital. Soewondo Kendal before and after giving anxiety generalist therapy. The research method used quasi experiment with pre post test without control group. Using the DASS questionnaire (Depression Anxiety Stress Scale) consisting of 14 questions related to anxiety. The research sample amounted to 60 families. Research results Respondents' characteristics were the majority of respondents in the age range 26-60 years, female, with the education level of the respondents mostly high school and the majority of respondents did not work. Relationships between clients and families are more dominated by relationships with spouses. Family ability in an effort to overcome the anxiety pretest mean 9.32 (SD 5.53) while at post test 11.28 mean (SD 5.61) with a value of p = value 0.002, which indicates that there is a change in the ability of families to overcome anxiety through anxiety generalist therapy. Suggestions for all families in particular to be able to apply generalist therapy that has been taught to help overcome anxiety in family members undergoing hemodialysis therapy.